The Association between the Police, Ambulance, Clinician Early Response (PACER) Model and Involuntary Detentions of People Living with Mental Illness: A Protocol for a Retrospective Observational Study - Julia Heffernan; Amy Pennay; Elizabeth Hughes; Richard Gray (MDPI AG, 2023)
Emergency services are frequently called to attend mental health incidents and are looking for innovative ways to improve their responses and reduce the burden on services. Involuntary detention of people living with mental illness is considered more frequent than necessary, leading to increased pressure on emergency departments, and is often a traumatic experience for patients. The Police, Ambulance, Clinician Early Response (PACER) model was developed in 2019 in Canberra, Australia, and seeks to reduce involuntary detentions by embedding a mental health clinician into emergency services as a mobile mental health crisis response intervention. This protocol details a retrospective cohort study that will examine the association between PACER and involuntary detentions using medical and police records and compare the results to standard ambulance and police responses. We will use relative risk and odds ratio calculations to determine the probability of being involuntarily detained or diverted from hospital; and we will describe the patient characteristics and outcomes in the PACER cohort. Results will be reported using the STROBE checklist for reporting cohort studies. This study was not registered on a publicly accessible registry.